Diagnóstico molecular de tuberculosis pélvica: reporte de caso (2012)
Tuberculosis is a re-emerging infectious disease. A retrospective analysis was made of the clinical history of a 48-year-old woman in April 2009; she was a secretary at a third-level hospital living in an urban area. Pelvic tubercular infection was suggested as a possible diagnosis; spoligotyping molecular methodology was used on a peritoneal secretion sample to confirm such diagnosis and confirmed the presence of Mycobacterium tuberculosis (octal code 777777777760771, SIT 53, Family T1).